A single-arm, open-label, intervention study to investigate the improvement of glucose tolerance after administration of the 5-aminolevulinic acid (5-ALA) in the patients with mitochondrial diabetes mellitus. Issue 10 (12th March 2021) - Nakamura, Yuta; Haraguchi, Ai; Shigeno, Riyoko; Ito, Ayako; Horie, Ichiro; Kawakami, Atsushi; Abiru, Norio
Abstract: Background: Mitochondrial diabetes mellitus (MDM) is characterized by maternal inheritance, progressive neurosensory deafness, insulin secretory disorder, and progressive microvascular complications. Mitochondria are critical organelles that provide energy in the form of adenosine triphosphate (ATP). An impairment of ATP production in pancreatic β cells is regarded as the main cause of the insulin secretory disorder in patients with MDM, and these patients require insulin replacement therapy early after the diagnosis. The amino acid 5-aminolevulinic acid (5-ALA), a precursor of heme metabolites, is a non-proteinogenic δ amino acid synthesized in mitochondria. An addition of ferrous iron to 5-ALA enhances heme biosynthesis and increases ATP production through an upregulation of the respiratory complex. Several studies have reported that the administration of 5-ALA and ferrous iron to existing treatment improved the glycemic control in both patients with prediabetes and those with type 2 diabetes mellitus. The additional administration of 5-ALA and ferrous iron to MDM patients on insulin therapy may improve their insulin secretory capacity and glycemic control by improving their mitochondrial function. The findings of this study are expected to provide new treatment options for MDM and improve the patients' glycemic control and prognosis. Methods/design: This study is a single-arm, open-label pilot intervention study using clinical endpoints to investigate the effects of treatment with 5-ALA plus sodium ferrous citrate (SFC) to patients with MDM on their glucose tolerance. A total of 5 patients with MDM will be administered 5-ALA/SFC (200 mg/d) for 24 weeks. We will perform a 75-g oral glucose tolerance test before and at 24 weeks after the start of this 5-ALA/SFC treatment to evaluate glucose-dependent insulin responses. Discussion: To the best of our knowledge, this study will be the first assessment of the effects of 5-ALA/SFC in patients with MDM. This study will obtain an evidence regarding the effectiveness and safety of 5-ALA/SFC for patients with MDM. Trial registration: This study was registered with the University Hospital Medical Information Network (UMIN000040581) on July 1, 2020 and with the Japan Registry of Clinical Trials (jRCTs071200025) on August 3, 2020.